PEMAKNAAN BONG PAY PADA WARGA KETURUNAN TIONGHOA DI KELURAHAN SUDIROPRAJAN SURAKARTA - Yulia Masruroh; Bagus Haryono; Argyo Demartoto (UNIVERSITAS SEBELAS MARET (UNS), 2015)
Chinese culture is one of the oldest in the world. Chinese people have many interesting culture from their ancestor which they keep to preserved until today, and one of it is the making of bong pay. Bong pay is a tomb which a Chinese people called it, is a construction that build on top of the grave give a meaning that somebody has died. For Chinese people, bong pay is not just a sign but also have another hidden symbolic meaning. The purpose of this research is (1) to describe the meaning of Bong Pay to Chinese descendent at Village Sudiroprajan of Surakarta, (2) describe the shift thing of bong pay meaning at present.This research is using a qualitative method with a phenomenological approach to obtain the source of information and data from descendants. The samples that had been taken were 4 people of Chinese descendants from Sudiroprajan village. The sampling technique is using purposive sampling. The data source that being used primary data that included the informant, places and the research location which is Sudiroprajan village. Another research is secondary which is data or records that supporting this research.The results of this research is (1) Chinese descendent people give a meaning to bong pay is a prove of love and respect to ancestor because ancestry is most glorifield in Confucianism, to Christian Chinese descent is a sign that a person has died not forgotten. As symbolic bong pay is describe as prestige ad social status for someone has died, because it’s take a lot of money to make it. Bong pay is given meaning as a symbol of identity because it can be identified with culture and tradition of Chinese. (2) there is shifting on the meaning of bong pay at the present. It happen because the changing of the religion from Chinese descendent people. That changing is affecting their behavior and acting on giving the meaning of bong pay. Key world : Bong Pay, Chinese Descendent People, Symbolic